Local industry watchdog sounds alarm over AI stealing South African data on LinkedIn - Schutters, Lindsey (Zawya, 2024)
The South African Artificial Intelligence Association (SAAIA) has called on the Information Regulator to investigate the use of South African user data by LinkedIn to train its artificial intelligence (AI) models without prior consent. This comes as the association seeks to promote responsible AI practices, ensuring that AI developments do not infringe on individual rights, particularly when it comes to the processing of personal data.
South Africa